2017
DOI: 10.1080/19440049.2017.1310396
|View full text |Cite
|
Sign up to set email alerts
|

Release of carbon nanoparticles of different size and shape from nanocomposite poly(lactic) acid film into food simulants

Abstract: Poly(lactic) acid (PLA) film with 2 wt% mixed carbon nanofillers of graphene nanoplates (GNPs) and multiwall carbon nanotubes (MWCNTs) in a weight ratio of 1:1 with impurities of fullerene and carbon black (CB) was produced by layer-to-layer deposition and hot pressing. The release of carbon nanoparticles from the film was studied at varying time-temperature conditions and simulants. Migrants in simulant solvents were examined with laser diffraction analysis and transmission electron microscopy (TEM). Film int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 34 publications
(40 reference statements)
0
14
0
1
Order By: Relevance
“…Thermal conductivity and diffusivity of GNP nanocomposites were improved by the addition of graphene nanoplatelets by 181% and 214%, respectively. Thermal transport in obtained PLA/GNP composites is a thriving area of research thanks to graphene's extraordinary heat conductivity properties and its In our previous studies [50][51][52] it was found that the PLA is still biodegradable and, only if there is a burning of composites (T < 850 • C), residual ash contains an amount of graphite and carbon nanotubes, creating concerns about environmental pollution and damage. A quantitative and qualitative risk assessment has been carried out in two cases-so-called "bad practices" (not in compliance with safety measures) and "good practices" (subject to modern safety measures).…”
Section: Discussionmentioning
confidence: 99%
“…Thermal conductivity and diffusivity of GNP nanocomposites were improved by the addition of graphene nanoplatelets by 181% and 214%, respectively. Thermal transport in obtained PLA/GNP composites is a thriving area of research thanks to graphene's extraordinary heat conductivity properties and its In our previous studies [50][51][52] it was found that the PLA is still biodegradable and, only if there is a burning of composites (T < 850 • C), residual ash contains an amount of graphite and carbon nanotubes, creating concerns about environmental pollution and damage. A quantitative and qualitative risk assessment has been carried out in two cases-so-called "bad practices" (not in compliance with safety measures) and "good practices" (subject to modern safety measures).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, during ultra-strong dynamic migration test [20] the release of nanoscale size particles (100 -1000 nm) from the GNP/MWCNT/PLA composite film is higher (0.5-0.7 number %) compared to (0.1-0.2 number %) nanoparticle migrants that was observed during the strong static migration test in the three food simulants, 3% acidic acid, 10% and 50% ethanol. The larger size nanoparticle migrants (1 -10 microns) were found also in higher amount (3 -5 number %) during the ultra-strong migration test, compared to 1-2 number % for the strong static test.…”
Section: Release Of Graphene and Carbon Nanotubes Due To Degradation mentioning
confidence: 64%
“…The characterization of such release provides critical information for environmental nanoobject exposure from biodegradable nanocomposites. In our previous studies [19][20][21], we have investigated the release of GNP and MWCNTs from the composite film GNP/MWCNT/PLA in alcoholic and acid food simulants, high temperature migration conditions, such as: (i) strong static migration test (with heating at 90 o C for 4 hours); and (ii) ultra-strong dynamic migration test (heating at 90 o C for 4 hours followed by subsequent storage for 10 days at 40°C, including dynamic treatment for 1 min daily). The strong static and ultra-strong dynamic migration conditions were set accordingly with the prescription in EU Regulation 10/2011 (EU 2011) [28] and literature sources [29,30] for migration of polymer films in food simulants.…”
Section: Release Of Graphene and Carbon Nanotubes Due To Degradation mentioning
confidence: 92%
See 2 more Smart Citations